Konkretisasi Kuliah Kerja Nyata Membangun Desa Merdeka pada Praktik Interprofessional Education di Fakultas Kesehatan : Sebuah Tinjauan Kualitatif - Devin Mahendika; Ema Julita; Panji Nalendra Hafizh Mahardika Stevan (Kelompok Ilmiah Hippocrates Fakultas Kedokteran Universitas Udayana, 2023)
ABSTRACT Introduction: Interprofessional Education (IPE) is a systematic pattern of adult interdisciplinary learning patterns to optimize health services. This research has a direction and aims to see the concretization of the Real Work Lecture (KKN) program to Build Independent Villages at the health faculty. Method: This research is a qualitative research, observational descriptive type. Samples were taken using a purposive sampling method. Result: From this research, it was found that the KKN for Developing Independent Villages has helped a lot in the practice of implementing IPE. It is evident from the results of the research that the same understanding is obtained from knowing all about adminsitration and implementation of IPE which has had an impact on the implementation of the health work program in the village environment for the implementing elements themselves. Discussion: The IPE learning concept teaches that two or more health professions work together in optimizing health services, pursuing competency knowledge, skills, attitudes, and teamwork. This form is applied in the Community Service Program to Build an Independent Village by providing the widest possible opportunity for participants to actively participate in the health development. Conclusion: All elements agree that this activity has a positive impact on the implementation of IPE, this program which makes the implementation of IPE successful. It is necessary in the future to make better improvements both in terms of important goals, the big picture, and even the process of realizing health in helping government performance. Keywords: Desa Merdeka, IPE, KKN